Biomass-based closed-pore hard carbon material, preparation method thereof and sodium-ion battery negative electrode material
By preheating and Joule heat treatment on biomass, closed-cell hard carbon materials with excellent electrochemical properties were prepared, which solved the problem of inappropriate pore structure and carbon layer spacing of hard carbon materials, and improved the energy of sodium ion batteries Density and cyclic performance, and achieve simplicity and efficiency of industrial production.
Patent Information
- Application Number
- CN202411617415.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-13
AI Technical Summary
When preparing hard carbon materials, the pore structure is not ideal, the carbon layer spacing is not suitable, and the defect control is insufficient, resulting in poor energy density and circulation performance of sodium ion batteries. The traditional method steps are complicated and energy consumption is high, making it difficult to meet. Industrial production demand.
Using biomass-based closed-cell hard carbon material preparation method, the biomass is converted into a structural framework with high carbonization ability through preheating preheating, and then Joule heat treatment is performed under an inert atmosphere to quickly generate an adjustable closed-cell and carbon layer spacing. and hard carbon materials with defective structures.
The storage performance of sodium ions is significantly improved, high initial Coulomb efficiency and high reversible capacity are achieved, technical defects in the existing preparation methods of the prior art, and the preparation process is simplified, reducing energy consumption and production costs.
Smart Images

Figure CN119218977A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials for sodium ion batteries, and in particular to a closed-cell hard carbon material based on biomass, a preparation method thereof, and a negative electrode material for sodium ion batteries. Background Art
[0002] Hard carbon materials have attracted extensive attention in sodium-ion battery negative electrode materials due to their unique structural properties. However, hard carbon materials prepared using existing technical methods usually face problems such as unsatisfactory pore structure, inappropriate carbon layer spacing, and insufficient defect control, which directly affects the energy density and cycle performance of sodium-ion batteries. In addition, the currently commonly used closed-pore generation technologies, such as chemical activation and chemical vapor deposition, have complex steps, long time and high energy consumption, which are difficult to meet the needs of industrial production.
[0003] It can be seen that biomass materials have become important precursors for the preparation of hard carbon materials because of their abundant sources, low cost and environmental friendliness. However, biomass-derived hard carbon materials prepared by traditional methods often have low yields due to insufficient carbonization process or difficulty in structural regulation, and the pore structure and carbon layer spacing are not conducive to sodium ion storage. In particular, the lack of simple and effective strategies to achieve the simultaneous regulation of closed pores, defects and carbon layer spacing has limited the practical application of biomass-based hard carbon materials.
[0004] The prior art also discloses a rapid preparation method for hard carbon negative electrode materials, such as the publication number CN116462176A, entitled: A super-fast preparation method for hard carbon negative electrode materials for sodium ion batteries; the disclosed method for preparing hard carbon negative electrode materials is: (1) drying and crushing the biomass raw material to obtain a hard carbon precursor; (2) purifying and drying the hard carbon precursor, wherein the purification treatment is water washing, alcohol solution washing, acid solution washing, and alkaline solution washing, and purifying at 20-80°C for 3-24h to obtain a purified hard carbon precursor; (3) ultra-rapid heat treatment of the purified hard carbon precursor in a protective environment based on the Joule heating effect to obtain a hard carbon negative electrode material. The method in this patent document is simple, has a short carbonization time, and can still maintain good electrochemical performance, but this patent does not provide closed pore or even pore structure data, so it is impossible to judge its technical effect.
[0005] The publication number is CN118771351A, and the title is: A method for rapidly preparing hard carbon negative electrode materials, the resulting products, and sodium ion batteries; the disclosed method for preparing hard carbon negative electrode materials is: (1) subjecting the preliminarily treated biomass material to low-temperature heating carbonization under an inert atmosphere to obtain a pre-carbonized material; (2) mixing the pre-carbonized material with an activator and subjecting the pre-carbonized material to Joule heating treatment under an inert atmosphere, wherein the activator is at least one of sodium hydroxide, sodium carbonate, potassium hydroxide, and potassium carbonate; and then acid-washing, water-washing, and drying the carbon material after ultrafast Joule heating treatment to obtain a hard carbon negative electrode material. The patent document discloses that, on the one hand, a microporous structure is etched on the surface of the carbon material by alkali activation, and then the closed-pore content of the material is increased by high-temperature treatment, thereby providing more sites for the material to store sodium, so that the prepared hard carbon material exhibits excellent electrochemical properties; on the other hand, the carbonaceous material is heated to a certain high temperature in a short time by instantaneous high-temperature Joule heating treatment, so that the raw material decomposes faster, and the rapid aggregation of metal impurities at high temperature is avoided, which is beneficial to the subsequent impurity removal, and the instantaneous high-temperature Joule heating can accelerate the diffusion of the alkali activator, promote the activation reaction more fully, and make the size and distribution of the etched pore structure more uniform, which is beneficial to the uniform stress distribution of the hard carbon material during the charge and discharge process, and improve the cyclic stability of the material. However, activation and acid washing are commonly used treatment methods in the preparation of carbon materials. Although they can significantly increase the specific surface area and porosity of hard carbon negative electrode materials, they also bring technical defects such as loss of hard carbon negative electrode materials, uncontrollable pore size distribution and high production costs. During the activation process, the action of strong alkali or salt activators will cause excessive corrosion of the hard carbon negative electrode material, while further cleaning by acid washing may aggravate the destruction of the pore structure, resulting in reduced yield and uneven pore size distribution of the hard carbon negative electrode material. In addition, multiple processing steps greatly increase the time and operating costs, and also put forward higher requirements for the environmentally friendly treatment of waste liquid. Summary of the invention
[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a biomass-based closed-cell hard carbon material and a preparation method thereof and a sodium ion battery negative electrode material. The present invention first preheats the biomass to convert the fragile biomass into a hard carbon precursor, which has a structural framework with high carbonization ability and abundant ultra-micropores. The hard carbon precursor is then subjected to Joule heat treatment to quickly generate a biomass-based closed-cell hard carbon material with adjustable closed pores, carbon layer spacing and defect structure. The biomass-based closed-cell hard carbon material prepared by the method of the present invention significantly improves the storage performance of sodium ions, has a high initial coulombic efficiency and a high reversible capacity, and overcomes the technical defects of the prior art preparation method and the hard carbon negative electrode material obtained by the preparation.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing a closed-cell hard carbon material based on biomass comprises the following steps:
[0009] The biomass is preheated in an inert atmosphere to obtain a hard carbon precursor with a high carbonization ability structural framework and abundant ultra-micropores;
[0010] Under an inert atmosphere, the hard carbon precursor is instantaneously heated by Joule heat treatment to quickly generate closed nanopores to obtain a biomass-based closed-pore hard carbon material.
[0011] Preferably, the preheating pretreatment condition is: heating at 350-600°C for 1-6h. The heating temperature is very important because the main thermal decomposition peak of cellulose is 300-400°C. The carbonization time is not the main influencing factor, as long as the carbonization is uniform, but if the carbonization time is too long, some micropores may begin to close or collapse, affecting the distribution of the pore structure and the specific surface area, and at the same time affecting the effect of the subsequent Joule heat treatment.
[0012] Preferably, the heating rate of the preheating pretreatment is 2-20°C / min. If the heating rate is too fast, the pore structure of the biomass-based closed-cell hard carbon material may be uneven, which will affect the subsequent generation of closed pores. A slow heating rate consumes energy and causes the biomass-based closed-cell hard carbon material to gradually decompose and shrink inside, thereby forming a denser carbon structure, resulting in a reduction in the number of micropores in the hard carbon precursor.
[0013] Preferably, the temperature of instantaneous heating is 1000-2000°C.
[0014] Preferably, the pulse width of Joule heat is instantaneous, and the pulse width is ≤60s. "Instantaneous" usually refers to a rapid heating process in an extremely short time (milliseconds or even microseconds); the number of pulses is 1-5 times, that is, it can experience 1-5 instantaneous heating. Influence of pulse width: The pulse width (the duration of each pulse) determines the heating intensity and heating time of the material in a short time, which directly affects the microstructure of the material. Short pulse width: A shorter pulse width will result in instantaneous high-temperature heating accompanied by rapid cooling. Such a rapid heating-cooling process can introduce more defects and closed-pore structures into the material while maintaining the amorphous characteristics of the material. Short pulses help to suppress the tendency to graphitize and maintain the disordered structure of hard carbon, so it is suitable for electrochemical applications that require high capacity and closed-pore structures. Long pulse width: A longer pulse width means longer heating, resulting in more time for structural rearrangement inside the material. This will prompt carbon atoms to form a more ordered structure that tends to graphitize. This heating method usually results in a reduction in the closed pores of the material and a weakening of the microporous structure, which is more suitable for applications requiring higher conductivity, but may reduce the specific surface area and closed pore structure of the material.
[0015] Effect of pulse number: The number of pulses determines the cumulative number of heating treatments and the total energy input, and also plays an important role in the overall properties of the material. A small number of pulses: If the number of pulses is small, the heating treatment of the material is more focused on the instantaneous high temperature effect. This will produce more micropores and defects, forming a loose hard carbon structure, which is conducive to electrolyte penetration and improves electrochemical activity. At the same time, low pulse numbers will not cause serious carbon rearrangement, maintain high closed porosity and amorphous structure, but the structural uniformity of the material may not be high. A large number of pulses: As the number of pulses increases, the material has time to partially cool between pulses, and the overall heating cumulative effect is more significant. This will increase the order and density of the material, tend to reduce the carbon layer spacing, make the material more dense and stable, but at the same time, if the carbon layer spacing is too low, the diffusion and embedding process of sodium ions will be significantly restricted, resulting in a decrease in sodium embedding capacity and the reversible capacity of the battery. Therefore, the number of pulses needs to be specifically adjusted according to the hard carbon precursor. In particular, the hard carbon precursors mentioned are applicable in the range of 1-5 pulses, and this range can be appropriately widened to meet different performance requirements. This flexible pulse control helps optimize the structural characteristics of biomass-based closed-pore hard carbon materials and further improve their sodium storage performance. In the present invention, a shorter pulse width and a smaller number of pulses are used to maintain the high closed-pore and defect characteristics of biomass-based closed-pore hard carbon materials with a rapid heating-cooling effect, which is suitable for electrochemical energy storage applications.
[0016] Preferably, the biomass is selected from cellulose nanocrystals, corn cobs, bamboo, hazelnut husks or coconut shells.
[0017] Preferably, corn cobs, bamboo, hazelnut shells or coconut shells are crushed to a particle size of ≤75 μm before use, i.e., the particles are sieved through a 200-mesh sieve after being crushed.
[0018] The present invention also protects the biomass-based closed-cell hard carbon material obtained by the above preparation method.
[0019] Preferably, the interlayer spacing of the biomass-based closed-cell hard carbon material is 0.35-0.44 nm.
[0020] The present invention also protects a sodium ion battery negative electrode material made of a biomass-based closed-pore hard carbon material.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention uses biomass as raw material, first preheats it at 350-600°C to obtain a hard carbon precursor with a high carbonization capacity structural framework and abundant ultra-micropores, and then performs Joule heat treatment on the hard carbon precursor at 1000-2000°C, undergoes instantaneous high-temperature carbonization to quickly generate closed nanopores, and quickly generates biomass-based closed-pore hard carbon materials with adjustable closed pores, carbon layer spacing and defect structures. The present invention proposes an innovative regulation method, specifically a closed-pore regulation method for biomass-derived hard carbon materials based on Joule heat. The method combines preheating pretreatment with Joule heat carbonization technology, and controls the pore structure and layer spacing of the biomass-based closed-pore hard carbon material by adjusting the preheating pretreatment temperature and the Joule heat treatment temperature to optimize the sodium ion storage performance, which is used to quickly prepare high-performance biomass-based closed-pore hard carbon materials.
[0023] 2. The present invention provides an efficient and simple preparation method. Compared with the prior art preparation method, only by adjusting the preheating pretreatment and Joule heat treatment temperature, it is possible to generate a hard carbon material with rich closed pores, suitable carbon layer spacing and controllable defect structure while shortening the preparation time and reducing energy consumption.
[0024] 3. The biomass-based closed-cell hard carbon material of the present invention exhibits a high initial coulombic efficiency of 93.1% and a high first-cycle reversible capacity of 367 mAh g -1 , especially suitable for high energy density sodium ion batteries, and has broad application prospects in the field of energy storage.
[0025] 4. The method of the present invention is universal and can be applied to the rapid conversion of a variety of biomass raw materials, including cellulose nanocrystals, coconut shells, hazelnut shells, corn cobs and bamboo. It provides a new approach for the preparation of high-performance hard carbon materials and shows wide adaptability and industrialization potential.
[0026] 5. Improving the yield of biomass-based closed-cell hard carbon materials is a key goal of improving the carbonization process in order to achieve higher material utilization and industrial application potential. The present invention optimizes the Joule heat treatment technology through preheating pretreatment. The present invention significantly improves the yield of biomass-based closed-cell hard carbon materials, makes the production process more efficient, and reduces the loss of biomass-based closed-cell hard carbon materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a pore structure diagram of the biomass-based closed-cell hard carbon material of Example 1, Examples 6-7 and the biomass-based hard carbon material of Comparative Example 1.
[0028] Figure 2 It is a comparison chart of the total carbonization yield of the closed-cell hard carbon materials based on biomass of Examples 1-5 and the hard carbon materials based on biomass of Comparative Examples 1-5.
[0029] Figure 3 This is a high-resolution transmission electron micrograph of the biomass-based closed-pore hard carbon material of Example 1.
[0030] Figure 4 This is a sodium storage performance diagram of the biomass-based closed-pore hard carbon material of Example 10 and the biomass-based hard carbon material of Comparative Example 1.
[0031] Figure 5 Graph showing the closed pore volumes of closed-pore hard carbon materials based on biomass in Example 1, Examples 8-9 and Comparative Example 6. DETAILED DESCRIPTION
[0032] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0033] In the present invention, the biomass is preheated, that is, heated to 350-600°C at a heating rate of 2-20°C / min and kept warm for 1-6 hours under an inert atmosphere to obtain a framework with high carbonization ability and rich ultra-microporous hard carbon precursors. The structure of the hard carbon precursor can be regulated by adjusting the preheating atmosphere, heating rate, holding temperature, and holding time.
[0034] The preheated hard carbon precursor is placed in a Joule heat heating device for instantaneous high-temperature treatment to form a biomass-based closed-pore hard carbon material with abundant closed pores, suitable carbon layer spacing and defect structure. The structure of the biomass-based closed-pore hard carbon material is regulated by adjusting the temperature, pulse width and number of pulses of the Joule heat.
[0035] The suitable carbon interlayer spacing is generally in the range of 0.37nm to 0.40nm. This spacing is larger than the standard interlayer spacing of graphite (about 0.335nm) and has the following advantages:
[0036] 1. Sodium ion embedding and diffusion: A suitable larger interlayer spacing can provide smoother embedding and diffusion channels for sodium ions and reduce diffusion resistance. This is crucial to sodium ion storage performance because the radius of sodium ions is larger than that of lithium ions, and a wider spacing is more suitable for their embedding.
[0037] 2. Closed-pore filling and stability: Wider interlayer spacing helps to form a stable closed-pore structure, allowing sodium ions to be stored in the closed pores more effectively, thereby improving the low-potential platform capacity.
[0038] 3. Cyclic stability: Appropriate interlayer spacing can also buffer the volume change during the insertion and release of sodium ions, reduce structural stress, extend the service life of biomass-based closed-cell hard carbon materials and improve the cyclic performance.
[0039] The defect structure can increase the specific surface area and is beneficial to the adsorption of sodium ions.
[0040] The technical solution of the present invention is further studied by using embodiments and comparative examples below. The specific research methods and results are as follows:
[0041] Example 1
[0042] A method for preparing a closed-cell hard carbon material based on biomass comprises the following steps:
[0043] S1. Preheating pretreatment: Place the cellulose nanocrystals in a tubular furnace, heat to 600° C. at a heating rate of 5° C. / min, and keep warm for 3 h in a nitrogen atmosphere to obtain a microporous hard carbon precursor.
[0044] S2. Joule heat carbonization: The hard carbon precursor is placed in a Joule heat carbonization device, instantaneously heated at 1500° C., and then directly cooled to obtain a biomass-based closed-cell hard carbon material, which is recorded as HC600-J-1500.
[0045] Example 2
[0046] A method for preparing a closed-cell hard carbon material based on biomass comprises the following steps:
[0047] S1. Preheating pretreatment: Wash, dry and crush the coconut shell to a particle size of ≤75 μm to obtain coconut shell powder. Heat the coconut shell powder to 600°C in a tubular furnace at a heating rate of 5°C / min and keep it warm for 3 hours under a nitrogen atmosphere to obtain a microporous hard carbon precursor.
[0048] S2. Joule heat carbonization: The hard carbon precursor is placed in a Joule heat carbonization device, instantaneously heated at 1500° C., and then directly cooled to obtain a biomass-based closed-cell hard carbon material.
[0049] Example 3
[0050] A method for preparing a closed-cell hard carbon material based on biomass comprises the following steps:
[0051] S1. Preheating pretreatment: Wash, dry and crush the corn cob to obtain corn cob powder with a particle size of ≤75 μm, heat the corn cob powder to 600°C in a tube furnace at a heating rate of 5°C / min, and keep it warm for 3 hours under an argon atmosphere to obtain a microporous hard carbon precursor.
[0052] S2. Joule heat carbonization: The hard carbon precursor is instantaneously heated at 1500° C. in a Joule heat carbonization device and then directly cooled to obtain a biomass-based closed-pore hard carbon material.
[0053] Example 4
[0054] A method for preparing a closed-cell hard carbon material based on biomass comprises the following steps:
[0055] S1. Preheating pretreatment: Wash, dry and crush the bamboo to obtain bamboo powder with a particle size of ≤75 μm. Heat the bamboo powder to 600°C in a tube furnace at a heating rate of 5°C / min and keep it warm for 3 hours under a nitrogen atmosphere to obtain a microporous hard carbon precursor.
[0056] S2. Joule heat carbonization: The hard carbon precursor is placed in a Joule heat carbonization device, instantaneously heated at 1500° C., and then directly cooled to obtain a biomass-based closed-cell hard carbon material.
[0057] Example 5
[0058] A method for preparing a closed-cell hard carbon material based on biomass comprises the following steps:
[0059] S1. Preheating pretreatment: Wash, dry and crush the hazelnut shell to obtain hazelnut shell powder with a particle size of ≤75 μm, heat the hazelnut shell powder to 600° C. at a heating rate of 5° C. / min in a tubular furnace, and keep it warm for 3 h under a nitrogen atmosphere to obtain a microporous hard carbon precursor.
[0060] S2. Joule heat carbonization: The hard carbon precursor is placed in a Joule heat heating device, instantaneously heated at 1500°C, and then directly cooled to obtain a biomass-based closed-pore hard carbon material.
[0061] Example 6
[0062] A method for preparing a closed-cell hard carbon material based on biomass comprises the following steps:
[0063] S1. Preheating pretreatment: Place the cellulose nanocrystals in a tubular furnace, heat to 350° C. at a heating rate of 5° C. / min, and keep warm for 3 h in a nitrogen atmosphere to obtain a microporous hard carbon precursor.
[0064] S2. The hard carbon precursor is placed in a Joule heat carbonization device, instantaneously heated at 1500° C., and then directly cooled to obtain a biomass-based closed-cell hard carbon material, which is recorded as HC350-J-1500.
[0065] Example 7
[0066] A method for preparing a closed-cell hard carbon material based on biomass comprises the following steps:
[0067] S1. Preheating pretreatment: Place the cellulose nanocrystals in a tubular furnace, heat to 400° C. at a heating rate of 5° C. / min, and keep warm for 3 h in a nitrogen atmosphere to obtain a microporous hard carbon precursor.
[0068] S2. The hard carbon precursor is placed in a Joule heat carbonization device, instantaneously heated at 1500° C., and then directly cooled to obtain a biomass-based closed-cell hard carbon material, which is recorded as HC400-J-1500.
[0069] Example 8
[0070] A method for preparing a closed-cell hard carbon material based on biomass comprises the following steps:
[0071] S1. Preheating pretreatment: Place the cellulose nanocrystals in a tubular furnace, heat to 600° C. at a heating rate of 5° C. / min, and keep warm for 3 h in a nitrogen atmosphere to obtain a microporous hard carbon precursor.
[0072] S2. The hard carbon precursor is placed in a Joule heat carbonization device, instantaneously heated at 1500° C., and then directly cooled to obtain a biomass-based closed-cell hard carbon material, which is recorded as HC600-J-1000.
[0073] Example 9
[0074] A method for preparing a closed-cell hard carbon material based on biomass comprises the following steps:
[0075] S1. Preheating pretreatment: Place the cellulose nanocrystals in a tubular furnace, heat to 600° C. at a heating rate of 5° C. / min, and keep warm for 3 h in a nitrogen atmosphere to obtain a microporous hard carbon precursor.
[0076] S2. Place the hard carbon precursor in a Joule heat carbonization device for instantaneous heating. After instantaneous heating at 2000° C., directly cool it to obtain a biomass-based closed-cell hard carbon material, which is recorded as HC600-J-2000.
[0077] Example 10
[0078] A method for preparing a closed-cell hard carbon material based on biomass comprises the following steps:
[0079] S1. Preheating pretreatment: Place the cellulose nanocrystals in a tubular furnace, heat to 600° C. at a heating rate of 5° C. / min, and keep warm for 3 h in a nitrogen atmosphere to obtain a microporous hard carbon precursor.
[0080] S2. The hard carbon precursor is placed in a Joule heat carbonization device, and after instantaneous heating at 1500° C. for 20 seconds, it is directly cooled to obtain a biomass-based closed-cell hard carbon material.
[0081] Embodiment 11
[0082] A method for preparing a closed-cell hard carbon material based on biomass comprises the following steps:
[0083] S1. Preheating treatment: The cellulose nanocrystals are placed in a tubular furnace, heated to 350° C. at a heating rate of 2° C. / min, and kept warm for 6 h in a nitrogen atmosphere to obtain a hard carbon precursor rich in micropores.
[0084] S2. Place the hard carbon precursor in a Joule heat carbonization device for instantaneous heating, keep the temperature at 1500° C. for 60 seconds, and pulse once to obtain a biomass-based closed-cell hard carbon material.
[0085] Example 12
[0086] A method for preparing a closed-cell hard carbon material based on biomass comprises the following steps:
[0087] S1. Preheating pretreatment: Place the cellulose nanocrystals in a tube furnace, heat to 600° C. at a heating rate of 20° C. / min, and keep warm for 1 hour in a nitrogen atmosphere to obtain a hard carbon precursor rich in micropores.
[0088] S2. Place the hard carbon precursor in a Joule heat carbonization device for instantaneous heating, keep it at 2000° C. for 30 seconds, and pulse it 5 times to obtain a biomass-based closed-cell hard carbon material.
[0089] Comparative Example 1
[0090] A method for preparing a biomass-based hard carbon material comprises the following steps:
[0091] The cellulose nanocrystals were placed in a Joule heat heating device for instantaneous heating at 1500°C and then directly cooled to obtain a biomass-based hard carbon material, which was recorded as HC25-J-1500.
[0092] Comparative Example 2
[0093] The preparation method of the biomass-based hard carbon material is the same as the preparation steps of Comparative Example 1, except that the cellulose nanocrystals are replaced with coconut shells, and comprises the following steps:
[0094] The coconut shell is washed, dried and crushed to a particle size of ≤75 μm to obtain coconut shell powder. The coconut shell powder is instantaneously heated at 1500°C and then directly cooled to obtain a biomass-based hard carbon material.
[0095] Comparative Example 3
[0096] The preparation method of the biomass-based hard carbon material is the same as the preparation steps of Comparative Example 1, except that the cellulose nanocrystals are replaced by bamboo, and comprises the following steps:
[0097] The bamboo is washed, dried and crushed to obtain bamboo powder with a particle size of ≤75 μm. The bamboo powder is instantaneously heated at 1500°C and then directly cooled to obtain a biomass-based hard carbon material.
[0098] Comparative Example 4
[0099] The preparation method of the biomass-based hard carbon material is the same as the preparation steps of Comparative Example 1, except that the cellulose nanocrystals are replaced with corn cobs, and includes the following steps:
[0100] The corn cob is washed, dried and crushed to obtain corn cob powder with a particle size of ≤75 μm. The corn cob powder is instantaneously heated at 1500°C and then directly cooled to obtain a biomass-based hard carbon material.
[0101] Comparative Example 5
[0102] The preparation method of the biomass-based hard carbon material is the same as the preparation steps of Comparative Example 1, except that the cellulose nanocrystals are replaced with hazelnut shells, and includes the following steps:
[0103] The hazelnut shells are washed, dried and crushed to obtain hazelnut shell powder with a particle size of ≤75 μm. The hazelnut shell powder is instantaneously heated at 1500° C. and then directly cooled to obtain a biomass-based hard carbon material.
[0104] Comparative Example 6
[0105] A method for preparing a closed-cell hard carbon material based on biomass comprises the following steps:
[0106] S1. Preheating pretreatment: Place the cellulose nanocrystals in a tubular furnace, heat to 600° C. at a heating rate of 5° C. / min, and keep warm for 3 h in a nitrogen atmosphere to obtain a microporous hard carbon precursor.
[0107] S2. Place the hard carbon precursor in a Joule heat carbonization device for instantaneous heating. After instantaneous heating at 2500° C., directly cool it to obtain a biomass-based closed-cell hard carbon material, which is recorded as HC600-J-2500.
[0108] Examples 1-12 of the present invention all produce biomass-based closed-cell hard carbon materials with abundant closed-cells, uniform closed-cells and suitable interlayer spacing. The following is a study of the biomass-based closed-cell hard carbon materials of Examples 1-10, and a comparative study with Comparative Examples 1-6. The specific research methods and results are as follows:
[0109] Performance comparison at different preheating temperatures and the same Joule heat treatment temperature (1500°C):
[0110] Figure 1The pore structure diagram under the same Joule heat treatment and different preheating conditions. Figure 1 The results show that as the preheating temperature increases, the closed-pore structure inside the biomass-based closed-pore hard carbon material increases. After a large number of ultra-micropores are initially generated at a higher preheating temperature (such as 600°C), more closed nanopores are formed after Joule heat treatment. Compared with the biomass-based hard carbon material that has not been preheated in Comparative Example 1, this increase in closed pores significantly improves the ability to store sodium ions.
[0111] In summary, the structure of closed-pore hard carbon materials based on biomass shows significant differences at different Joule heat treatment temperatures. The Joule heat treatment temperature of 1500℃ achieves a good balance between the closed-pore structure, interlayer spacing and defect level, which helps to improve the sodium ion storage performance. Although the higher temperature (2000℃) improves the graphitization degree and conductivity, it is not conducive to the embedding and storage of sodium ions due to the reduction of closed pores and interlayer spacing.
[0112] The yields of Examples 1-5 and Comparative Examples 1-5 are as follows Figure 2 As shown, the results indicate that preheating treatment can significantly improve the stability of biomass-based closed-cell hard carbon materials, making them have higher carbonization ability, thereby reducing carbon loss during subsequent Joule heat treatment.
[0113] Figure 3 In order to test the pore structure of the obtained biomass-based closed-cell hard carbon material using transmission electron microscopy (TEM), Figure 3 The results show that biomass-based closed-pore hard carbon materials have sufficient closed pores, which are surrounded by carbon layers and form a stable nano-enclosed structure, which is conducive to the storage of sodium ions.
[0114] Figure 4 1 is a comparison diagram of the electrochemical performance of the closed-cell hard carbon material based on biomass in Example 10 and the hard carbon material based on biomass in Comparative Example 1. The electrochemical performance test method is as follows: the closed-cell hard carbon material based on biomass in Example 10 and the hard carbon material based on biomass in Comparative Example 1 are mixed with sodium alginate (the mass ratio of the two is 95:5) in deionized water, and then the slurry is coated on a copper foil to prepare the slurry. After drying overnight, the slicing is used as a working electrode, and the slicing is assembled into a half-cell with the sodium sheet. The electrolyte in the half-cell is 1.0 mol L -1 A solution of NaPF6 in diethanol dimethyl ether at 25 mA g -1 The charge and discharge cycles were performed at a constant current density.
[0115] Figure 4 The results show that the biomass-based closed-cell hard carbon material in Example 1 exhibits an initial coulombic efficiency of 93.1% and a first-cycle reversible capacity of 367 mAh g in sodium-ion batteries.-1 Comparative Example 1: The initial Coulombic efficiency of the biomass-based hard carbon material is 64.7%, and the first-cycle reversible capacity is 142 mAh g -1 Compared with Comparative Example 1, the electrochemical performance of Example 1 is significantly improved.
[0116] Performance comparison at the same preheating temperature (600℃) and different Joule heat treatment temperatures:
[0117] Figure 5 The closed-cell structure diagram under different Joule heat treatment and the same preheating conditions. Figure 5 The results show that a lower preheating temperature (1000°C) generates fewer closed-cell structures. When the preheating temperature is increased, the number of closed cells increases significantly, and the pore size is larger and more evenly distributed, indicating that the rapid thermal shock at this temperature effectively promotes the transformation of ultra-micropores to closed cells. However, due to the high temperature causing the carbon layer to rearrange, when the temperature reaches 2000°C and 2500°C, the interlayer spacing is further reduced, the degree of graphitization of biomass-based closed-cell hard carbon materials is improved, and the structure is more compact, which limits the insertion and extraction of sodium ions and has an adverse effect on the electrochemical performance.
[0118] Compared with the prior art publication number CN118771351A, entitled: A method for rapidly preparing hard carbon negative electrode materials and the resulting products and sodium ion batteries, the initial coulombic efficiency and reversible capacity of the present invention are higher than any embodiment of publication number CN118771351A, indicating that under the preparation conditions of the present invention, by regulating the conditions of preheating pretreatment and Joule heat carbonization, it has better electrochemical properties and achieves better technical effects.
[0119] In addition, in order to find a balance between performance and production cost, the present invention introduces an optimized preheating pretreatment scheme. Compared with the traditional activation and pickling method, the preheating pretreatment scheme of the present invention can achieve the regulation of pore structure with fewer processing steps, effectively improving the yield and closed-cell ratio. The preheating pretreatment enhances the carbonization ability of biomass-based closed-cell hard carbon materials by controlling temperature and time, making the structure more heat-resistant, thereby reducing the phenomenon of excessive decomposition during Joule heat treatment. At the same time, this scheme avoids the strong corrosive effect of the activator and the possible pore destruction during pickling, making the pore size distribution of biomass-based closed-cell hard carbon materials more uniform, which helps to construct a closed-cell structure and improve the specific capacity and first-cycle coulomb efficiency of biomass-based closed-cell hard carbon materials. In addition, the operating time and cost required for multiple processing steps in the patent with publication number CN118771351A are reduced, and the amount of waste liquid discharged is reduced, thereby significantly reducing the production cost while improving the performance of biomass-based closed-cell hard carbon materials, achieving an effective balance between performance and economy.
[0120] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a closed-cell hard carbon material based on biomass, characterized in that: The steps include: In an inert atmosphere, the biomass is preheated at 350-600°C to obtain a hard carbon precursor with a carbonization capable structural framework and ultra-micropores; In an inert atmosphere, the hard carbon precursor is instantaneously heated at 1000-2000° C. using Joule heat treatment, and closed nanopores are quickly generated to obtain a biomass-based closed-pore hard carbon material.
2. The method for preparing a biomass-based closed-cell hard carbon material according to claim 1, characterized in that: The heating time for preheating treatment is 1-6h.
3. The method for preparing a biomass-based closed-cell hard carbon material according to claim 1, characterized in that: The preheating treatment was carried out at 600°C.
4. The method for preparing a biomass-based closed-cell hard carbon material according to claim 1, characterized in that: Joule heat treatment was applied at 1500°C.
5. The method for preparing a biomass-based closed-cell hard carbon material according to claim 1, characterized in that: The pulse width of the Joule heat treatment is instantaneous, the pulse width is ≤60s, and the pulse number is 1-5 times.
6. The method for preparing a biomass-based closed-cell hard carbon material according to claim 1, characterized in that: The biomass is selected from cellulose nanocrystals, corn cobs, bamboo, hazelnut husks or coconut shells.
7. The method for preparing a biomass-based closed-cell hard carbon material according to claim 6, characterized in that: Corn cobs, bamboo, hazelnut shells or coconut shells should be crushed to a particle size of ≤75μm before use.
8. A biomass-based closed-cell hard carbon material obtained by the preparation method according to any one of claims 1 to 7.
9. The biomass-based closed-cell hard carbon material according to claim 8, characterized in that The interlayer spacing of biomass-based closed-pore hard carbon materials is 0.35-0.44 nm.
10. A negative electrode material for a sodium ion battery, characterized in that: Made from the biomass-based closed-cell hard carbon material as claimed in claim 8.
Citation Information
Patent Citations
Method for preparing carbon nano bar based on cellulose nanocrystals
CN106587006A
Preparation method of low-polarization sodium-ion battery hard carbon negative electrode material
CN117720093A
Sodium-ion battery bio-based hard carbon material and preparation method and application thereof
CN118515265A
Method for rapidly preparing hard carbon negative electrode material, obtained product and sodium ion battery
CN118771351A
Cited By
Method for preparing porous carbon material from aldose-saccharide compound, porous carbon material and application
CN120057893A
Sodium ion battery, sodium ion hybrid capacitor, hard carbon material and preparation method thereof
CN122561904A